Relapsing Superwarfarin Coagulopathy in an Unrecognised Early Pregnancy: An Eight-Month Vitamin K₁ Course Ending in Second-Trimester Pregnancy Loss - Arya Baruna Purwa Sunu; Ni Made Renny Anggreni Rena (Phlox Institute: Indonesian Medical Research Organization, 2026)
Background: Superwarfarins are anticoagulant rodenticides whose hepatic sequestration and enterohepatic recirculation produce a vitamin K–dependent coagulopathy lasting months. Exposure during pregnancy is rarely reported. Objective: To describe relapsing superwarfarin coagulopathy in a woman whose pregnancy was unrecognised at exposure, and to define the endpoint of antidotal therapy. Case presentation: An 18-year-old woman presented with two weeks of spontaneous ecchymoses, gum bleeding and haematuria. Haemoglobin was 6.0 g/dL with normal platelets and hepatic and renal function; prothrombin time (PT; >90 s) and international normalised ratio (INR; >6) exceeded the analytical ceiling and activated partial thromboplastin time (APTT) was 133.4 s. She later disclosed ingesting a rodenticide three days before onset. After 28 days of plasma, red cells and intramuscular vitamin K₁ she was discharged (INR 5.32) but relapsed 20 days later (haemoglobin 9.4→4.0 g/dL). Ultrasonography for suspected intraperitoneal bleeding instead disclosed an unsuspected live intrauterine pregnancy of 11 weeks, conceived around the time of ingestion. Despite parenteral vitamin K₁ the INR rebounded to 21.6 on day 10 before responding to high-dose infusion. Oral vitamin K₁ was titrated across 16 visits and withdrawn after eight months; the pregnancy was lost as an incomplete abortion at 18 weeks. Conclusion: Superwarfarin poisoning should be considered in any unexplained vitamin K–dependent coagulopathy; treatment must target the hepatic toxicant reservoir rather than symptom resolution, and maternal biochemical rescue does not guarantee fetal survival.